Enhancing Real Estate Data Analytics Education with Digital Badges - Jeffrey G. Robert; Marc R. Zaldivar; Helen Ajao; Zhenhuan Yang (Journal of Real Estate Practice and Education)
Real Estate statistical courses provide foundational content for students in business programs to be proficient in data analytics and management science skills. Not only are these skills essential for future real estate finance and investment analysis courses, but also they are highly demanded by real estate employers. However, students seem to have low motivation to learn real estate statistics, despite the clear need for the skills. We redesigned an entry-level real estate statistics course in an R1 higher education institution in the United States to integrate digital badges into the curriculum to test their influence on student motivation. We adopted a convergent parallel mixed methods research design using a finite population sampling survey and individual semi-structured interviews to evaluate our research questions. After surveying over eighty students and conducting interviews with thirty students, students reported positive sentiments towards digital badges and stated that the integration of digital badges in this real estate course improved their learning through enhanced motivation. We posit that digital badging may improve student outcomes across all quantitative real estate courses through enhanced student motivation.